Proses Loading Dan Discharging Di Terminal Petikemas Koja - Dhiyananda Haniifah Putri; Widyanur Handari; Surya Alam; Jerremy Vincen Errol; Siti Sahara (Peneliti.net, 2023)
The loading process at TPK Koja is the activity of loading or transferring cargo from the pier to the ship. Meanwhile, the usage process at TPK Koja is the activity of unloading or transferring cargo from the ship to the wharf. In the current reality, the many problems that occur during the loading or discharging process that are not in accordance with the procedure will affect the smooth running of the process. This problem is basically caused by various factors. The results of this observation aim to find out what things affect the smooth loading and unloading process and can reduce the risk of accidents or other emergencies.